Peningkatan Keaktifan Siswa Menggunakan Strategi Problem Based Learning pada Mata Pelajaran IPA kelas II di MI MUhammadiyah 01 Payaman - Anggun Hilma Awfanie; Oriza Zativalen; Ahmad Ipmawan Kharisma (Jurnal Tematik, 2026)
This research was motivated by the low level of student engagement in science learning in third-grade students at MI Muhammadiyah 01 Payaman. The objective of this study was to improve student engagement through the implementation of Problem-Based Learning (PBL) strategies. The method used was Classroom Action Research (CAR), implemented in two cycles. Each cycle included planning, implementation, observation, and reflection. The subjects were 22 third-grade students. Data were collected through observation, questionnaires, and documentation, then analyzed using descriptive quantitative methods. The results showed an increase in student engagement in each cycle after the implementation of the PBL strategy. The average student engagement score increased from 65.50 in cycle I to 72.17 in cycle II. Therefore, it can be concluded that the implementation of the Problem-Based Learning strategy has proven effective in increasing student engagement in science learning in third-grade students at MI Muhammadiyah 01 Payaman.